Measurement‐guided volumetric dose reconstruction for helical tomotherapy. (8th March 2015) - Stambaugh, Cassandra; Nelms, Benjamin; Wolf, Theresa; Mueller, Richard; Geurts, Mark; Opp, Daniel; Zhang, Geoffrey; Moros, Eduardo; Feygelman, Vladimir
Abstract : It was previously demonstrated that dose delivered by a conventional linear accelerator using IMRT or VMAT can be reconstructed — on patient or phantom datasets — using helical diode array measurements and a technique called planned dose perturbation (PDP). This allows meaningful and intuitive analysis of the agreement between the planned and delivered dose, including direct comparison of the dose‐volume histograms. While conceptually similar to modulated arc techniques, helical tomotherapy introduces significant challenges to the PDP formalism, arising primarily from TomoTherapy delivery dynamics. The temporal characteristics of the delivery are of the same order or shorter than the dosimeter's update interval (50 ms). Additionally, the prevalence of often small and complex segments, particularly with the 1 cm Y jaw setting, lead to challenges related to detector spacing. Here, we present and test a novel method of tomotherapy‐PDP (TPDP) designed to meet these challenges. One of the novel techniques introduced for TPDP is organization of the subbeams into larger subunits called sectors, which assures more robust synchronization of the measurement and delivery dynamics. Another important change is the optional application of a correction based on ion chamber (IC) measurements in the phantom. The TPDP method was validated by direct comparisons to the IC and an independent, biplanar diode array dosimeter previously evaluated for tomotherapy delivery quality assurance. Nineteen plans with varying complexity were analyzed for the 2.5 cm tomotherapy jaw setting and 18 for the 1 cm opening. The dose differences between the TPDP and IC were 1.0 % ± 1.1 % and 1.1 % ± 1.1 %, for 2.5 and 1.0 cm jaw plans, respectively. Gamma analysis agreement rates between TPDP and the independent array were: 99.1 % ± 1.8 % (using 3% global normalization/3 mm criteria) and 93.4 % ± 7.1 % (using 2% global/2 mm) for the 2.5 cm jaw plans; for 1 cm plans, they were 95.2 % ± 6.7 % (3% G/3) and 83.8 % ± 12 % (2% G/2). We conclude that TPDP is capable of volumetric dose reconstruction with acceptable accuracy. However, the challenges of fast tomotherapy delivery dynamics make TPDP less precise than the IMRT/VMAT PDP version, particularly for the 1 cm jaw setting. PACS number: 87.55Qr